Faith and Fracture: Exploring the Imamship Scuffle in Ojo Town, Lagos State, Nigeria - Raji, Mubin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper delves into the intricate dynamics of faith and conflict as it pertains to the Imamship discord in Ojo, Lagos State, Nigeria. By examining the historical, socio-economic and political contexts surrounding the leadership of the mosque, this study illuminates the underlying factors contributing to the fractious nature of religious authority in the community. Through qualitative method approach, combining indepth interviews, community dialogues, archival research and participant observations, the study investigates the underlying causes, consequences and implications of the leadership crisis within the Muslim community. Findings reveal that the dispute not only reflects theological disagreements but also exposes underlying socio-economic tensions and power struggles. The study identifies competing interpretations of Islamic leadership, generational divides and external influences as critical factors contributing to the scuffle. The paper argues that addressing these fractures requires a thorough understanding of the cultural and historical context, emphasizing the need for dialogue and reconciliation within the community. The study proposes recommendations for resolving the Imamship scuffle, emphasizing: inclusive leadership selection processes, knowledge transfer and contextualized Islamic education. Ultimately, this study seeks to foster a deeper understanding of how faith intersects with social challenges, offering insights that are crucial for conflict resolution and community cohesion in Ojo and similar contexts in Nigeria.